An analysis on the factors on CO2 Emission in the top five carbon emitting countries - Mok, Jing Wei (2024)
Climate change is one of the global issues today. Carbon dioxide emission is one of the main causes of global climate change. This study investigates the effects of per capita GDP, population growth, energy consumption and renewable energy consumption on carbon dioxide emissions in the top five carbon emitting countries from 1990 to 2020. In this study, panel data was analyzed by using quantitative research design and second-hand data to evaluate the relationship between these variables and their impact on carbon dioxide emissions. The survey results show that population growth, energy consumption and per capita GDP have significantly increased carbon dioxide emissions, highlighting the key role of economic activities in environmental degradation. On the contrary, the increase of renewable energy consumption is associated with the decrease of carbon dioxide emissions. The results show that renewable energy can be effectively used as a strategy to slow down climate change. The significance of this study is very important for policy makers and stakeholders to formulate strategies to deal with the dual challenges of economic development and environmental sustainability in the context of global climate change.